Simplify the product using the distributive property.

(3p + 2)(5p - 1)

simplify the product
(2y - 5) (3y + 1)
can someone help point me in the right direction, with this COVID-19 going around i havent had much time for school, and now it started back up and i forgot how to do these?

2 answers

(3p + 2)(5p - 1) = 3p(5p-1) + 2(5p-1)
= 16p^2 - 3p + 10p - 2
now just simplify, and do the other the same way.
If necessary, review the distributive property.
You got to FOil
(3p+2)(5p-1)
3p*5p=15p^2
3p*-1=-3p
2*5p=10p
2*-1=-2
So the answer is 15p^2+7p-2